Sistem Pemodelan Flow Rate Control Menggunakan Teknologi 4.0 di Laboratorium Instrumentasi PTKI Medan - Mansyur Mansyur; Said Hanief; Dian Kurnia; Toba Sastrawan Manik; Yanto Yanto (CV MEDAN TEKNO SOLUSI, 2023)
Fluid flow rate measurement is a measurement to obtain data for analysis because in principle fluid is pressurized energy which is increasingly being developed by industry. Each method of measuring flow rate will produce a different characteristic value, not all types of flow rate measurement can use the same method, judging from the resulting pressure drop it will influence each method used. In this research, flow rate control and data reconciliation were carried out on pipe merging. When measuring fluids, pipe connections such as elbows with a certain slope are often found. The slope of the elbow, orifice and venturi can affect the pressure difference or pressure drop in the fluid that passes through the elbow. The research also carried out a flow rate control system through the orifice plate and a transmitter as a sensor. Then it will be developed to measure flow rates using sensing elements using a microcontroller and display monitoring using a computer. Reconciliation is carried out with flow rate as a measurement variable to prove that the flow rate is as desired or with the set point. The data will be stored directly on the computer device. The results of the test showed that the highest error value for the flowmeter 4.0 was 1.9 with a set point value of 40%. For the PID value, P is 1.999, while I is 999 and D is 100, which is the most optimal PID value and shows the fastest results.